RETRACTED: Logo design: lessons learned from interbrand's top 100 global brands - Alrasheed Saleh Suleiman; Siddiqui Kamran (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001